1993
DOI: 10.1029/93gl01975
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous observations of subauroral electron temperature enhancements and electromagnetic ion cyclotron waves

Abstract: Observational results from an investigation of low frequency (0.5–4.0 Hz) electromagnetic ion cyclotron waves and subauroral electron temperature enhancements recorded from the DE‐2 satellite are presented. Four different wave events were analyzed, all recorded at magnetic latitudes from 57–60°, magnetic local times from 8–14 hours, and altitudes from 600–900 km. The peak wave amplitudes during the events ranged from 8–70 nT and 5–30 mV/m in the magnetic and electric field, respectively. Electron temperature (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…It is worth noting that Iyemori and Hayashi [1989] and Erlandson et al [1993] observed down‐going electromagnetic waves with ∼0.1–1 Hz frequencies (Pc1 range) at L ≥ 4 in the dusk and morning sectors. Erlandson et al [1993] suggested that those are electromagnetic ion cyclotron (EMIC) waves generated by RC protons in the RC‐plasmasphere overlap region. Could this mechanism contribute to formation of the down‐going Poynting flux and energetic ion precipitations in the dusk‐evening sector (Figure 6)?…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that Iyemori and Hayashi [1989] and Erlandson et al [1993] observed down‐going electromagnetic waves with ∼0.1–1 Hz frequencies (Pc1 range) at L ≥ 4 in the dusk and morning sectors. Erlandson et al [1993] suggested that those are electromagnetic ion cyclotron (EMIC) waves generated by RC protons in the RC‐plasmasphere overlap region. Could this mechanism contribute to formation of the down‐going Poynting flux and energetic ion precipitations in the dusk‐evening sector (Figure 6)?…”
Section: Discussionmentioning
confidence: 99%
“…There are three leading mechanisms: Coulomb collisions of plasmaspheric electrons with RC ions producing a heated plasmaspheric electron population [Cole, 1965[Cole, , 1975Kozyra et al, 1987;Fok et al, 1993]; heating the plasmaspheric electrons through resonant Landau damping of electromagnetic ion cyclotron (EMIC) waves generated by RC ions [Cornwall et al, 1971; Thorne and Horne, 1992;Zhou et al, 2013]; and kinetic Alfvén waves directly accelerating plasmaspheric electrons into the ionosphere through the parallel electric field associated with the waves [Hasagawa and Mima, 1978]. Evidences of ion cyclotron, kinetic Alfvén waves in association with events of ionospheric electron heating elsewhere have been reported [Lundblad and Søraas, 1978;Erlandson et al, 1993;Lanzerotti et al, 1978;Mishin and Burke, 2005]. Although the energy source of plasmaspheric electron heating is assumed to be in the magnetosphere [Kozyra et al, 1997], to our knowledge few in situ evidence of plasmaspheric electron heating in the plasmaspheric plume has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Using measured ring current and plasmasphere particle distributions in conjunction with a hydromagnetic model, both Gorbachev et al [1992] and Khazanov et al [1994] have derived ionospheric electron and ion temperature profiles expected from the generation of equatorial ion cyclotron waves which match well with measured profiles. Evidence of ion cyclotron waves in association with ionospheric heating events have been reported by Lundblad and Søraas [1978] and Erlandson et al [1993]. Both Jordanova et al [2001] and Khazanov et al [2003] have included the generation of ion cyclotron waves in two‐dimensional ring current models.…”
Section: Introductionmentioning
confidence: 99%